Akuntabilitas Pengelolaan Alokasi Dana Desa (ADD): Studi Kasus : Desa Tikonu Kecamatan Wundulako Kabupaten Kolaka - Taslim Fait; Anis Ribcalia Septiana; Rustam Tohopi (Sawala : Jurnal Administrasi Negara, 2021)
The purpose of this study was to determine the Accountablity of Fund Allocation Management (ADD) in Tikonu Village, Wundulako District, Kolaka Regency. The method used in this research is descriptive qualitative. research location in Tikonu village, Wundulako sub-district, Kolaka regency. The informants in this study were the Village Head, the Head of the BPD, the Chair of the LPM, the Village Secretary, the Village Treasurer, the Head of Development, Members of the BPD, Members of the LPM, TPK, Community Leaders and the community of Tikonu Village, Wundulako District, Kolaka Regency. Types and sources of primary research data obtained directly from research informants through data collection techniques, and secondary data obtained through library research, namely by inventorying and analyzing literature in the form of books, magazines and newspapers related to the problems under study. The results show that the village government of Tikonu has not fully implemented the accountability model for managing village fund allocations, seen from the completion of monthly reports that have passed the deadline and the village community has not been fully involved in the implementation of village meetings on village fund allocation, so there has not been good cooperation between village government and village communities as mandated in Kolaka Regent Regulation Number 04 of 2017. Lack of village community involvement in the preparation of village development plans using village fund resulting in development in Tikonu village not running optimally for the benefit of all its residents. All the problems that occur indicate the need for Village Fund Allocation management to be carried out in a participatory, transparent and accountable manner based on the Kolaka Regent Regulation Number 04 concerning the use and implementation of Village Fund Allocation. The process of implementing development programs through the Village Fund Allocation (ADD) should involve youth organizations, youth leaders and the community.